PENGARUH METODE PEMBELAJARAN TERHADAP PENGETAHUAN LINGKUNGAN HIDUP DITINJAU DARI KREATIVITAS SISWA (Eksperimen pada Siswa Kelas X SMA Negeri Surakarta) - Suwarto WA. (Program Studi Pendidikan Kependudukan dan Lingkungan Hidup, 2010)
The development of knowledge and techonology increases the quality of human life. However, it may causeproblems of the environment is damaged due to the lack of environmental awareness. One of the ways toovercome the problems is by integrating environmental education in Biology subject for SMA students. Thisexperimental research was intended to study the effects of learning methodes and student creativity on studentenvironmental knowledge. The study was carried out at SMA Negeri Surakarta 2009 involving 10th gradestudents. Results were as follow: 1) Students who were taught through problem-based learning (PBL) methodhad better knowledge of environment than those through telling method, 2) Students with any levels (high levelor low level) of creativity had better knowledge of environment if they were taught through PBL method, 3)There was a significant interaction between learning method used and student creativity and their environmentalknowledge.